Dynamic antisymmetry and the syntax of noun incorporation - Barrie, Michael; SpringerLink (Online service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
This innovative analysis of noun incorporation and related linguistic phenomena does more than just give readers an insightful exploration of its subject. The author re-evaluates and forges links between two influential theories of phrase structure: Chomsky's Bare Phrase Structure and Richard Kayne's Antisymmetry. The text details how the two linguistic paradigms interact to cause differing patterns of noun incorporation across world languages. With a solid empirical foundation in its close reading of Northern Iroquoian languages especially, Barrie argues that noun incorporation needs no special mechanism, but results from a symmetry-breaking operation. Drawing additional data from English, German, Persian, Tamil and the Polynesian language Niuean, this synthesis has major implications for our understanding of the formation of the verbal complex and the intra-position (roll-up) movement. It will be priority reading for students of phrase structure, as well as Iroquoian language scholars.
Dynamic Antisymmetry and the Syntax of Noun Incorporation; Introduction; Outlook and Goals; Noun Incorporation; Properties of NI; On the Syntactic Nature of NI; Conclusion and Outline of Book;- Theoretical Background; A Bit of History of Phrase Structure; Bare Phrase Structure; Antisymmetry; Head Movement; Alternative Accounts of Linearization; Demerge and Concatenate: SOV as Underlying Order; Parameterized Order; Departures from LCA; Conclusion;- Unifying Antisymmetry and Bare Phrase Structure; The Problem of Mutual C-command; Previous Accounts; Guimarães (2000) and Self-Merge; Nunes and Uriagereka (2000); Richards (2001); Conclusion;- The LCA and BPS;- Proposal;- Alternatives to Complement-to-Spec Roll-up; Spec-to-Spec Movement and Romance Clitics; Avoidance of the Initial Merger Problem; Linearization and Late Insertion; Summary;- Noun Incorporation in Northern Iroquoian; Northern Iroquoian Languages; Clause Structure of Northern Iroquoian; Nominal Structure in Northern Iroquoian; Patterns of NI in Northern Iroquoian; Productivity of NI; Nominal Roots; Analysis; Previous Analyses; NI As Phrasal Movement; Properties of Iroquoian NI; NI IN Ditransitives; NI and Overt DPs; Conclusion;- Noun Incorporation and its Kind in Other Languages; The Structure of Nominals and V/IN Order; NI in Sierra Popoluca; English Gerunds; Description of NI in English Gerunds; German Progressives; Persian Long Infinitive Constructions; Tamil Noun Incorporation and Coordination; Adverb Incorporation in Blackfoot; Conclusion;- V+N Order; Polynesian Pseudo Noun Incorporation; The Structure of Niuean; Pseudo Noun Incorporation; Postlude on Tukang Besi; Romance Compounds; Description of V+N Compounds; Mapudungun; Upriver Halkomelem; Conclusion;- Conclusion; Summary; Limitations; Conclusions and Implications;-Subject Index.
Electronic reproduction.
Keywords: Grammar, Comparative and general -- Noun; Grammar, Comparative and general -- Syntax; Generative grammar; Phrase structure grammar; Asymmetry (Linguistics).; Electronic books